Causes of Hospitalization and Death among Newly Diagnosed HIV-Infected Adults in Thailand - Sukonthip Chanto (2020)
© The Author(s) 2020. More than half of newly diagnosed HIV-infected patients enter to care with a low CD4 count. A retrospective cohort study was conducted among newly diagnosed HIV-infected adults who were hospitalized. Of 148 patients, median (interquartile range [IQR]) age was 39.3 (30.5-47.1) years and 114 (77%) patients were male. Baseline median (IQR) CD4 count was 79 (24-218) cells/mm3. The median (IQR) length of hospital stay was 8 (4-16) days. Half of the patients were hospitalized with AIDS-defining illness (ADI). Common opportunistic infections were Pneumocystis jirovecii pneumonia (20.3%) and tuberculosis (18.9%). CD4 count was statistically significantly associated with hospitalization with ADI (odds ratio: 0.85, per 10 cells/mm3 increased; 95% confidence interval: 0.80-0.90). The mortality was 5.4%. In conclusion, half of newly diagnosed Thai HIV-infected patients were hospitalized with ADI. Early detection of HIV infection leading to early antiretroviral therapy initiation and prevention of serious complications is essential.